Hippocampus and amygdala volumes are reduced in patients with schizoaffective disorder - Gurok, M. Gurkan; Aksoy, Dilek Bakis; Mermi, Osman; Korkmaz, Sevda; Tabara, Muhammed Fatih; Yildirim, Hanefi; Atmaca, Murad (Elsevier Ireland Ltd, 2024)
We aimed to examine the hippocampus and amygdala volumes in patients with schizoaffective disorder with the notion that schizoaffective disorder has strong resemblance of clinical presentation with schizophrenia and bipolar disorder and that there have been studies on regions of interest volumes in patients with schizophrenia and bipolar disorder but not in patients with schizoaffective disorder. Eighteen patients with schizoaffective disorder and nineteen healthy controls were included into the study. Hippocampus and amygdala volumes were examined by using the MRI. Both hippocampus and amygdala volumes were statistically significantly reduced in patients with schizoaffective disorder compared to those of the healthy control comparisons (p<0.001 for the hippocampus and p<0.001 for the amygdala). In summary, our findings of the present study suggest that patients with schizoaffective disorder seem to have smaller volumes of the hippocampus and amygdala regions and that our results were in accordance with those obtained both in patients with schizophrenia and bipolar disorder, considering that schizoaffective disorder might have neuroanatomic similarities with both schizophrenia and bipolar disorder. Beacuse of some limitations aforementioned especially age, it is required to replicate our present results in this patient group.
Keywords: Schizoaffective disorder; MRI; Hippocampus; Amygdala